The quest for systematization in educational psychology practice—the case of SDQ - Szulevicz, Thomas; Arnfred, Jon Busck (Frontiers in Psychology, 2025)
IntroductionThe field of Educational Psychology (EP) practice is currently shaped by debates on the balance between systematized and situated approaches. This study explores these debates through the lens of the Strengths and Difficulties Questionnaire (SDQ).MethodsUtilizing data from a current research project, the application of the SDQ in EP practice was analyzed. The study involved analyses of SDQ responses and psychoeducational reports and interviews with educational psychologists who used the SDQ in their assessments.ResultsThe findings indicate that the participating educational psychologists were generally satisfied with the use of the SDQ. Additionally, a significant portion of the SDQ responses suggested that many of the examined children exhibited symptoms warranting further investigation for ADHD.DiscussionThe article concludes with a discussion on the dual perspectives regarding the systematic use of the SDQ. On one hand, there are arguments for its systematic application On the other hand, while a standardized use of the SDQ ensures systematic information, the questionnaire also contributes to a specific framing of the issue. It is crucial to recognize that the SDQ, originally developed by a child psychiatrist and not specifically designed for EP practice, frames the understanding of issues in a predominantly psychiatric manner. This can lead to a narrow focus on diagnosing and treating perceived deficiencies, potentially overlooking the broader educational and contextual factors that influence student wellbeing.